Development and Stability of Insecticide Resistance in the Leafminer Liriomyza trifolii (Diptera: Agromyzidae) to Cyromazine, Abamectin, and Spinosad. Issue 1 (22nd September 2014) - Ferguson, J. Scott
Abstract : Three populations of the leafminer, Liriomyza trifolii (Burgess), were collected from commercial ornamental production greenhouses in the United States and tested for susceptibility to three commercial insecticides. A leaf dip bioassay of leaves containing young (1–2-d-old) larvae was used. Based on larval mortality and compared with a susceptible laboratory reference colony, the three strains varied in spectrum and level of resistance to the insecticides. CA-1, collected from Gerbera daisy, was moderately resistant to cyromazine (18.1-fold) and abamectin (22.0-fold), but highly resistant to spinosad (>188-fold). CA-2, collected from chrysanthemums, was not resistant to abamectin, had a low level of resistance to cyromazine (8.2-fold), but was extremely resistant to spinosad (1, 192-fold). GA-1, collected from chrysanthemums, had very low levels of resistance to cyromazine (5.4-fold) and spinosad (1.9-fold) but was moderately resistant to abamectin (30.6-fold). When reared in the absence of insecticide selection pressure, all three strains reverted to approximately the level of the reference strain. The CA-1 strain reverted in nine generations to cyromazine; however, the lowest levels of abamectin and spinosad resistance reverted to was 3.1-fold at F8 and 3.2 at the F10, respectively. The CA-2 strain reverted in five generations to both cyromazine and spinosad. GA-1 reverted in five generations to abamectin. Based on the results, resistance to these three insecticides was unstable. Additionally, there was no cross-resistance among these three insecticides.